The impact of age on outcome in phase III NRG Oncology/RTOG trials of radiotherapy (XRT) +/− systemic therapy in locally advanced head and neck cancer. Issue 6 (July 2021) - Kish, Julie A.; Zhang, Qiang; Langer, Corey J.; Nguyen-Tân, Phuc Felix; Rosenthal, David I.; Weber, Randal S.; List, Marcy A.; Wong, Stuart J.; Garden, Adam S.; Hu, Kenneth; Trotti, Andy M.; Bonner, James A.; et al.
Abstract: Purpose: To examine the role age plays in the treatment and prognosis of locally advanced head and neck cancer (LAHNC) treated definitively with radiation alone or combined modality therapy. Methods: A retrospective analysis was performed of three NRG/RTOG trials examining either radiation alone or combined radiation and systemic therapy for LAHNC. The effect of age (≥70 yrs.) on cause-specific survival (CSS), overall survival (OS), and toxicity was evaluated. Results: A total of 2688 patients were analyzed, of whom 309 patients (11.5%) were ≥ 70. For all studies combined, the hazard ratio (HR) for CSS for patients age ≥ 70 vs. those <70 was 1.33 (95%CI: 1.14–1.55, p < 0.001). For OS, the HR for patients age ≥ 70 vs. those <70 for all studies combined was 1.55 (95% CI 1.35–1.77, p < 0.001). After adjustment for all covariates, age ≥ 70 was associated with worse OS regardless of adjustment for smoking and p16 status. The survival difference was more pronounced in those receiving combined radiation and systemic therapy. Hematologic and renal toxicities were increased in combined modality trials in patients ≥70 years old. Conclusions: Patients age ≥ 70 with LAHNC were underrepresented in these clinical trials. Their CSS and OS proved inferior to patients <70 years old.